The Political Economy of Reform during the Ramos Administration (1992-98) - Bernardo, Romeo L.; Tang, Marie-Christine G. (World Bank, Washington, DC, 2017)
This paper is one of several case studies prepared for the World Bank. The objective of the case studies is to provide the Commission on Growth and Development insights on the policy reform process in developing countries that give rise to economic growth. In contrast to other countries where economic reforms ushered in a long period of sustained growth, there is no such episode in Philippine economic history. Since the restoration of democracy in 1986, the Philippines under the Ramos administration came closest to breaking out of its 'sick man of Asia' image. The confidence generated by the administration among local and international players and analysts resulted from wide-ranging reforms rooted primarily in a sound macroeconomic and investor-friendly regime as well as global competitiveness. This study is not intended as a scorecard of the Ramos Administration. Rather, it concentrates on three specific sector reforms during the Ramos administration that demonstrate the elements of successful reform processes. These reforms not only helped to free up demands on public finances then- considered, in today's parlance, the 'binding constraint' on needed public investment and reduced risk premium to encourage private investments-but over time brought gains, some unforeseen and broader in terms of positive spillover effects on the rest of the economy, and linkage to overall growth today.